Design and Test of Quad-Bundle Spacer Damper Based on a New Rubber Structure - Zhenbing Zhao; Bin Liu; Shengchun Liu; Dachuan Zhang (Shock and Vibration)
Aiming at improving the handling efficiency and acquiring the satisfactory antivibration effect and damping performance, a quad-bundle spacer damper of 500 kV extra high voltage transmission lines was designed and developed based on a new rubber structure. Firstly, a mathematical vibration model of the spacer damper was constructed, and the structures of the defect-prone parts of the spacer damper were analyzed. Then, the structure was optimized based on the defect analysis, the clamp with fast installation as well as removal and the damper joint with superior performance were designed. On this basis, a new quad-bundle spacer damper was developed. Last but not least, the handling efficiency of the new quad-bundle spacer damper was evaluated, and performance tests were conducted according to the IEC standards. The evaluation and test results show that the handling efficiency, antivibration effect, and damping performance of the new quad-bundle spacer damper are significantly improved compared with those of the regular quad-bundle spacer damper, which provides a guarantee for the safe operation of 500 kV extra high voltage transmission lines.